Realizacja projektu „Zdolni z Pomorza” w Pomorskiej Bibliotece Pedagogicznej w Gdańsku .......... 133 - Malinowska, Klaudia (Skąd się biorą czytelnicy?, 2025)
THE IMPLEMENTATION OF THE ŁÓDŹ PROVINCE CIVIC BUDGET PROJECTS ‘ŁÓDZKIE NA PLUS’ WITH THE EXAMPLE OF THE ŁĘCZYCA BRANCH OF THE PEDAGOGICAL LIBRARY IN ZGIERZThe article analyzes two projects financed from the Łódź Province Civic Budget ‘Łódzkie na plus’ in the Pedagogical Library in Zgierz with a special focus on the effectiveness of the efforts and the commitment of the local community. Two projects were implemented in 2020 and 2023, respectively: ‘Uważni w sieci… kształtowanie bezpiecznych zachowań w Internecie mieszkańców powiatu łęczyckiego” (Careful online: forming secure Internet behaviors among the residents of the Łęczyca District; 2020) and ‘Rehabilitacja książką sposobem na radzenie sobie w życiu” (Health recovery with books as a copying strategy, 2023). The realization of the civicbudget was described together with the practices that may prove useful for other libraries which seek to be, or currently are, in the process of doing civil budget projects.